Preparation method of heat-resistant aluminum-lithium alloy with high product of strength and elongation and aluminum-lithium alloy
Through reasonable Cu, Sc, Zr composition ratio and multi-stage thermal processing technology, a high-strength plastic deposit-resistant aluminum-lithium alloy was prepared, which solved the problems of insufficient strength and brittle fracture of existing heat-resistant aluminum-lithium alloys in high temperature environments, and achieved high tensile strength, elongation and strong plastic deposit-resistant properties.
Patent Information
- Application Number
- CN202510324243.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-19
AI Technical Summary
The existing heat-resistant aluminum-lithium alloys are insufficient in high temperature environments and are prone to brittle fracture after heat exposure, which lacks the properties of high strength, high plasticity and high strength plasticization.
Through reasonable Cu, Sc and Zr composition ratios, combined with two-stage homogenization treatment, preliminary hot rolling, medium-temperature solid solution, aging treatment and high-temperature solid solution treatment processes, a high-strength plastic deposit-resistant aluminum lithium alloy was prepared. This process can basically dissolve the brittle phase, and the Sc and Zr elements enter the aluminum matrix in solid solution form, improve the roughening resistance of the nano T1 phase, and enhance the heat resistance and plasticity of the alloy.
After 100 hours of long-term thermal exposure test at 250°C, the tensile strength of the alloy is not less than 346MPa, the elongation rate is not less than 15.6%, and the strong plasticization is not less than 5397.6MPa%, which is significantly better than existing commercial aluminum-lithium alloys.
Smart Images

Figure CN119824345A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum alloy materials, and in particular to a preparation method of a high-strength, plastic-product, heat-resistant aluminum-lithium alloy and an aluminum-lithium alloy. Background Art
[0002] Due to the demand for energy conservation and equipment lightweighting, the research and development of lightweight structural materials has become increasingly important. Among them, aluminum-lithium alloys have the advantages of low density, high strength, and high elastic modulus, and are now widely used in the aerospace field. The current third-generation aluminum-lithium alloys are mainly used in the front, middle, and rear fuselages of aircraft, floor beams, seat rails, boundary beams, cabin floors, and other structural parts with a service temperature below 150°C. Such usage restrictions are attributed to the insufficient strength of the third-generation aluminum-lithium alloys in high temperature environments (over 175°C), mainly because the thermal coarsening of the strengthening phase Al2CuLi-T1 phase causes its strength to decay rapidly at high temperatures. The fuselage skin, tail wing, and load-bearing frame near the engine of supersonic aircraft have stringent requirements for long-term service performance at 250°C, so the development of heat-resistant aluminum-lithium alloys is of great significance to further promote the lightweighting of aerospace equipment.
[0003] At present, the research and development of heat-resistant aluminum-lithium alloys is in its infancy. The general idea is to add transition metal elements and rare earth elements to form a large number of high-melting-point compounds in the aluminum matrix to improve the high-temperature strength of aluminum-lithium alloys, such as adding Fe elements to form Al3Fe phase, adding Mn, Zr, Sc and Er elements to form Al6Mn, Al 20 Cu2Mn3, Al8Cu4Sc phase and Al3(Sc,Zr,Er) phase, adding Ce to form Al8Cu4Ce phase, etc. Although these methods improve the heat resistance of aluminum-lithium alloys by introducing high melting point compounds, they ignore the damage of these brittle phases to the plasticity of aluminum-lithium alloys after thermal exposure. Moreover, compared with conventional aluminum alloys, aluminum-lithium alloys are more prone to brittle fracture after thermal exposure, mainly because the Li element will be concentrated at the grain boundary during thermal exposure, reducing the atomic bonding force between the grain boundaries.
[0004] The heat resistance design of structural parts not only considers high strength to counteract deformation caused by external forces, but also high plasticity is indispensable, which can greatly improve the safety of structural parts. If there is only heat resistance but lacks heat resistance and plasticity, once the force exceeds a certain limit, brittle fracture will easily occur, which will undoubtedly bring catastrophic consequences to the flight mission. Therefore, it is of great significance to develop heat-resistant aluminum-lithium alloys that can maintain high strength, high plasticity and high strength-plasticity product after heat exposure. Summary of the invention
[0005] The purpose of the present application is to provide a method for preparing a high-strength-plasticity heat-resistant aluminum-lithium alloy and an aluminum-lithium alloy, which can maintain high strength-plasticity, high plasticity and high strength after heat exposure.
[0006] To achieve the above objectives, this application provides the following technical solutions: A method for preparing a high-strength, high-plasticity, heat-resistant aluminum-lithium alloy comprises the following steps: Step 1: smelting the ingredients according to the alloy composition, casting and forming an ingot, wherein the ingot includes, by mass percentage, Cu 1.8-2.5%, Li 0.8-1.2%, Mg 0.1-0.5%, Sc 0.1-0.2%, Zr 0.05-0.15%, other impurity elements ≤0.1%, and the balance is Al, performing a two-stage homogenization treatment on the ingot, and then performing a peeling treatment on the ingot to obtain a peeled ingot; Step 2: preliminarily hot rolling the peeled ingot at 450-470° C., and after the hot rolling, oil-quenching the hot-rolled billet to room temperature within 15 seconds to complete medium-temperature solution treatment; Step 3, performing a first aging treatment on the rolled slab after the medium temperature solution treatment; Step 4, heating the rolled billet after the first aging treatment to 220-250° C. for insulation, and performing medium-temperature hot rolling at 220-250° C.; Step 5, performing high temperature solution treatment, wherein the temperature of the high temperature solution treatment is 7-12°C lower than the melting point of the aluminum-lithium alloy; Step six, performing 3-6% cold stretching pre-deformation, and then performing a second aging treatment to obtain the aluminum-lithium alloy.
[0007] Furthermore, in the two-stage homogenization treatment, the temperature of the first stage homogenization treatment is 400-420°C, the insulation time is 12-24 hours, and the temperature of the second stage homogenization treatment is 450-500°C, the insulation time is 15-30 hours.
[0008] Furthermore, before the preliminary hot rolling, the ingot is preheated at 450-470° C. for 3-10 hours.
[0009] Furthermore, the reduction amount of hot rolling is 20-40%, and the number of rolling passes is 2-4 times.
[0010] Furthermore, the temperature of the first aging treatment is 100-120° C., and the treatment time is 15-20 hours.
[0011] Furthermore, the insulation time of step 4 is 1 to 3 hours.
[0012] Furthermore, the reduction of the medium temperature hot rolling is 40-60%, and the number of rolling passes is 4-7 times.
[0013] Furthermore, the high temperature solution treatment time is 1 to 1.5 hours.
[0014] Furthermore, the temperature of the second aging treatment is 150-165° C., and the treatment time is 15-25 hours.
[0015] A high-strength-plasticity heat-resistant aluminum-lithium alloy, which is the aluminum-lithium alloy obtained according to any of the above-mentioned preparation methods of the high-strength-plasticity heat-resistant aluminum-lithium alloy. After a long-term heat exposure test at 250°C for 100 hours, its tensile strength is not less than 346MPa, its elongation is not less than 15.6%, and its strength-plasticity product is not less than 5397.6MPa%.
[0016] This application has the following advantages: (1) The present invention adopts a reasonable composition ratio of Cu, Sc and Zr, combined with a high temperature solution treatment process in which the solution temperature is only 7-12°C lower than the melting point, so that the brittle phases such as Al8Cu4Sc phase, primary Al3Sc, Al3Zr and Al3(Sc,Zr) phase in the matrix can be basically dissolved, which is beneficial to the heat resistance and plasticity.
[0017] (2) After the above-mentioned brittle phase is dissolved, Sc and Zr elements enter the aluminum matrix in the form of solid solution. These slow-diffusion elements can inhibit the diffusion of Cu elements, improve the coarsening resistance of the nano-T1 phase, and are beneficial to heat resistance.
[0018] (3) The addition of Sc and Zr elements, combined with the thermal processing technology of "initial hot rolling-medium temperature solution treatment-aging treatment-warm rolling", can suppress the recovery and recrystallization of dislocations during the hot processing to the greatest extent, increase the distortion energy, and refine the grain size of the alloy after high temperature solution treatment. At the same time, a large number of subgrain boundaries are retained, increasing the grain boundary density, which can dilute the grain boundary damage caused by the segregation of Li elements at the grain boundaries and is beneficial to the heat resistance and plasticity.
[0019] (4) Through the above-mentioned coordinated design of "alloy composition-hot working process-high temperature solution treatment process", the heat-resistant aluminum-lithium alloy of this application has a tensile strength of not less than 346MPa, an elongation of not less than 15.6%, and a strength-ductility product of not less than 5397.6MPa after a long-term heat exposure test at 250°C for 100h. Currently, the strength-ductility products of commercial aluminum-lithium alloys 8090 and 2090 are approximately 2856MPa and 2960MPa, respectively, after a long-term heat exposure test at 250°C for 100h. It can be seen that the advantages of this application are obvious. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 This is a TEM photograph of the precipitation phase constructed in the matrix after “initial hot rolling-medium temperature solution treatment-aging treatment” in Example 1.
[0022] Figure 2 The SEM photos of Example 1, Example 2, Comparative Example 2 and Comparative Example 4 after high temperature solution treatment, wherein: Figure 2 (a) is a SEM photograph of the aluminum-lithium alloy of Example 1 after high-temperature solid solution treatment; (b) is a SEM photograph of the aluminum-lithium alloy of Example 2 after high-temperature solid solution treatment; Figure 2 (c) is a SEM photo of the aluminum-lithium alloy of comparative example 2 after solution treatment; Figure 2 (d) is the SEM photograph of the aluminum-lithium alloy of comparative example 4 after high temperature treatment.
[0023] Figure 3 The inverse pole figures (IPF figures) and grain boundary distribution diagrams of Example 1 and Comparative Examples 1 to 3 after high-temperature solution treatment are shown in FIG. Figure 3 (a1) is the IPF diagram of the aluminum-lithium alloy of Example 1 after high temperature solution treatment; Figure 3 (a2) is the grain boundary distribution diagram of the aluminum-lithium alloy of Example 1 after high temperature solution treatment; Figure 3 (b1) is the IPF diagram of the aluminum-lithium alloy after thermal exposure test of Comparative Example 1; Figure 3 (b2) is the grain boundary distribution diagram of the aluminum-lithium alloy of comparative example 1 after high temperature solution treatment; Figure 3 (c1) is the IPF diagram of the aluminum-lithium alloy of comparative example 2 after high temperature solution treatment; Figure 3 (c2) is the grain boundary distribution diagram of the aluminum-lithium alloy of comparative example 2 after high temperature solution treatment; Figure 3 (d1) is the IPF diagram of the aluminum-lithium alloy of comparative example 3 after high temperature solution treatment; Figure 3 (d2) is the grain boundary distribution diagram of the aluminum-lithium alloy of comparative example 3 after high-temperature solution treatment.
[0024] Figure 4 This is a TEM photograph of the subgrain boundary of Example 1 after long-term heat exposure test.
[0025] Figure 5 TEM photos of the matrix precipitation phase of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4 after long-term heat exposure test, wherein: Figure 5 (a) is a TEM photo of the matrix precipitation phase of the aluminum-lithium alloy of Example 1 after heat exposure test; Figure 5 (b) is a TEM photo of the matrix precipitation phase of the aluminum-lithium alloy of Comparative Example 1 after thermal exposure test; Figure 5 (c) is a TEM photo of the precipitated phase of the aluminum-lithium alloy of comparative example 2 after heat exposure test; Figure 5(d) is a TEM photograph of the matrix precipitation phase of the aluminum-lithium alloy of comparative example 4 after heat exposure test.
[0026] Figure 6 These are the fracture photos of Example 1 and Comparative Examples 1 to 3 after long-term heat exposure test, where: Figure 6 (a) is a fracture photo of the aluminum-lithium alloy after tensile testing in Example 1; Figure 6 (b) Figure 6 (a) Local magnification of the marked area; Figure 6 (c) is a fracture photo of the aluminum-lithium alloy of comparative example 1 after tensile testing; Figure 6 (d) is a fracture photo of the aluminum-lithium alloy of comparative example 2 after tensile testing; Figure 6 (e) is a fracture photo of the aluminum-lithium alloy of comparative example 3 after tensile testing. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be described clearly and completely below. The following embodiments are merely examples for clearly illustrating the technical solution of the present application, and are not intended to limit the present application.
[0028] A method for preparing a high-strength, high-plasticity, heat-resistant aluminum-lithium alloy comprises the following steps: Step 1: Melt the ingredients according to the alloy composition, and cast the ingot to obtain the ingot. In terms of mass percentage, the ingot includes: Cu 1.8~2.5%, Li 0.8~1.2%, Mg 0.1~0.5%, Sc 0.1~0.2%, Zr 0.05~0.15%, other impurity elements ≤0.1%, and the balance is Al. After adding Sc and Zr elements, secondary Al3Sc, Al3Zr, Al3(Sc,Zr) L12 phases can be generated in the two-stage homogenization process, which play a role in inhibiting dislocation recovery and recrystallization in the subsequent hot rolling process. If the content of Cu, Sc or Zr elements is too high, a large amount of insoluble primary Al8Cu4Sc phase, primary Al3Sc, Al3Zr, Al3(Sc,Zr) phase will be formed, and these brittle phases will seriously endanger the plasticity of the alloy. After the components of this application are combined with high-temperature solution treatment only 7~12°C below the melting point, the brittle intermediate phase can be basically dissolved. The ingot is subjected to two-stage homogenization treatment, the temperature of the first stage homogenization treatment is 400-420°C, the holding time is 12-24 hours, and the temperature of the second stage homogenization treatment is 450-500°C, the holding time is 15-30 hours. Then the ingot is subjected to peeling treatment to obtain peeled ingot.
[0029] Step 2: preheat the ingot at 450-470℃ for 3-10 hours, and perform preliminary hot rolling at 450-470℃, with a reduction of 20-40% and 2-4 passes. After hot rolling, the hot-rolled billet is oil-quenched to room temperature within 15s to complete medium-temperature solution treatment. Preliminary hot rolling can close ingot defects, improve ingot quality, and lay the foundation for subsequent medium-temperature rolling; oil-quenching after hot rolling can play the role of medium-temperature solution treatment.
[0030] Step 3: Perform the first aging treatment on the rolled billet after the medium temperature solution treatment, the temperature is 100-120°C, and the treatment time is 15-20 hours. This step can construct a nano-aging phase Al2CuLi-T1 phase in the aluminum matrix.
[0031] Step 4: Heat the rolled billet after the first aging treatment to 220-250°C for 1-3 hours. Perform medium-temperature hot rolling at 220-250°C, with a reduction of 40-60% and 4-7 rolling passes. During medium-temperature hot rolling, the nano-T1 phase will further aggravate the dislocation pile-up, hinder the slip and climb of dislocations, and cooperate with the L12 phase formed during the homogenization process to inhibit the recovery and recrystallization of dislocations, increase deformation distortion energy, increase the nucleation driving force of subsequent high-temperature solution treatment, and refine the grain size. Compared with cold rolling, medium-temperature rolling can improve the deformation ability of the rolled billet and reduce the risk of cracking; compared with hot rolling, it can weaken the thermal motion of dislocations, reduce dislocation annihilation, and is also conducive to storing distortion energy.
[0032] Step five, high temperature solution treatment, the temperature of high temperature solution treatment is relatively high, only 7~12℃ lower than the melting point of aluminum-lithium alloy. The melting point of the alloy can be measured by differential thermal analysis or calculated by thermal simulation software. High temperature solution treatment at a temperature 7~12℃ lower than the melting point of the alloy can basically dissolve the primary brittle phase and dissolve as many Sc and Zr elements as possible. These slow diffusion elements will reduce the diffusion rate of Cu elements and increase the coarsening resistance of the T1 phase, thereby improving the heat resistance of the alloy. The solution temperature of aluminum-lithium alloy is usually selected to be 30~50℃ lower than the melting point to avoid coarse grains and reduce the plasticity of the alloy. After the composite addition of Sc and Zr elements, the secondary L12 phase formed during the homogenization process can pin the grain boundary migration during the high temperature solution treatment, inhibit grain growth, and ultimately ensure that the alloy grain size is less than 15μm, and at the same time can retain a large number of subgrain boundaries and increase the grain boundary density.
[0033] Step six, perform 3-6% cold stretching pre-deformation, and then perform a second aging treatment at a temperature of 150-165°C for 15-25 hours to obtain an aluminum-lithium alloy.
[0034] Example 1 A method for preparing a high-strength, high-plasticity, heat-resistant aluminum-lithium alloy comprises the following steps: Step 1: Smelt pure aluminum, pure lithium, pure magnesium, aluminum-scandium master alloy, and aluminum-zirconium master alloy under argon conditions, and cast them to obtain ingots. In terms of mass percentage, the ingots include: Cu 2.4%, Li 1.0%, Mg 0.4%, Sc 0.19%, Zr0.13%, other impurity elements 0.1%, and the balance Al. The ingots are subjected to two-stage homogenization treatment, the first stage of homogenization treatment is homogenized at 400°C for 12 hours, and the second stage of homogenization treatment is homogenized at 450°C for 15 hours. After the homogenization treatment, the ingots are peeled to obtain peeled ingots.
[0035] Step 2: preheat the peeled ingot at 450°C for 5 hours, and hot roll the ingot at 450°C with a reduction of 40% and 3 passes. After hot rolling, the hot-rolled billet is oil-quenched to room temperature within 15 seconds.
[0036] Step 3: Place the quenched billet into a 120° C. aging furnace for the first aging treatment for 15 hours to obtain a billet.
[0037] Step 4: Heat the billet to 250°C and keep it at this temperature for 2 hours. Perform medium-temperature hot rolling at 250°C, with a reduction of 50% and 4 rolling passes.
[0038] Step 4: The melting point of the alloy was calculated to be 572° C. using ThermoCalc software. After high temperature solution treatment at 563° C. for 1.5 hours, a solution sample was obtained.
[0039] Step 5: The solution sample is subjected to 5% cold stretching pre-deformation, and then aged at 165°C for 25 hours to obtain an aluminum-lithium alloy.
[0040] The aluminum-lithium alloy of this embodiment was subjected to a long-term heat exposure test, specifically: after the sample was heat exposed at 250° C. for 100 hours, a room temperature tensile property test was performed. The mechanical properties of the sample are shown in Table 1.
[0041] The microstructure of the aluminum-lithium alloy of this embodiment was characterized. The data of the grain size, grain boundary density after high temperature solution treatment and T1 phase size after heat exposure test are shown in Table 1.
[0042] The TEM photo of the precipitated phase in the matrix structure of the aluminum-lithium alloy in this embodiment after "preliminary hot rolling-medium temperature solid solution-aging treatment" is as follows: Figure 1 The SEM photo of the aluminum-lithium alloy after high temperature solution treatment in this embodiment is shown in Figure 2 The IPF diagram and grain boundary distribution diagram of the aluminum-lithium alloy after high-temperature solution treatment in this embodiment are shown in FIG. Figure 3 (a1, a2). The TEM photo of the subgrain boundary of this embodiment after long-term heat exposure test is as follows Figure 4The TEM photo of the matrix precipitation phase of the aluminum-lithium alloy in this embodiment after the heat exposure test is shown in FIG. Figure 5 (a) is shown. The fracture photo of the aluminum-lithium alloy after tensile testing in this embodiment is shown in Figure 6 As shown in (a,b).
[0043] Example 2 A method for preparing a high-strength, high-plasticity, heat-resistant aluminum-lithium alloy comprises the following steps: Step 1: pure aluminum, pure lithium, pure magnesium, aluminum-scandium master alloy, and aluminum-zirconium master alloy are melted under argon conditions and cast to obtain ingots. In terms of mass percentage, the ingots include: Cu 1.9%, Li 1.0%, Mg 0.3%, Sc 0.12%, Zr 0.08%, other impurity elements 0.1%, and the balance Al. The ingots are subjected to two-stage homogenization treatment, the first stage homogenization treatment is carried out at 420°C for 15 hours, and the second stage homogenization treatment is carried out at 460°C for 18 hours. After the homogenization treatment, the ingots are peeled to obtain peeled ingots.
[0044] Step 2: preheat the peeled ingot at 460°C for 3 hours, and hot roll the ingot at 460°C with a reduction of 30% and 3 passes. After hot rolling, the hot-rolled billet is oil-quenched to room temperature within 15 seconds to complete medium-temperature solution.
[0045] Step three, placing the quenched billet into an aging furnace at 110° C. for the first aging treatment for 15 hours to obtain a billet.
[0046] Step 4: Heat the billet to 230°C and keep it at that temperature for 2 hours. Perform medium-temperature hot rolling at 230°C, with a reduction of 55% and 5 rolling passes.
[0047] Step 5: The melting point of the alloy is calculated to be 588° C. by using ThermoCalc software. A high temperature solid solution treatment is performed at 578° C. for 1.5 hours to obtain a solid solution sample.
[0048] Step six, subjecting the solution sample to 6% cold stretching pre-deformation, and then aging treatment at 160°C for 25 hours to obtain an aluminum-lithium alloy.
[0049] The aluminum-lithium alloy of this embodiment was subjected to a long-term heat exposure test, specifically: after the sample was heat exposed at 250° C. for 100 hours, a room temperature tensile property test was performed. The mechanical properties of the sample are shown in Table 1.
[0050] The microstructure of the aluminum-lithium alloy of this embodiment was characterized. The data of the grain size, grain boundary density after high temperature solution treatment and T1 phase size after heat exposure test are shown in Table 1.
[0051] The SEM photo of the aluminum-lithium alloy after high temperature solution treatment in this embodiment is as follows Figure 2 (b) as shown.
[0052] Comparative Example 1 The invention discloses an aluminum-lithium alloy Al-2.5Cu-1.1Li-0.38Mg, without adding Sc and Zr elements.
[0053] Conventional hot working and heat treatment processes are used, including the following preparation steps: (1) Argon protection melting and metal mold casting to obtain ingots. (2) The ingot is homogenized at 400°C for 17 hours, then homogenized at 470°C for 22 hours, and then the ingot is peeled. (3) The ingot is preheated at 460°C for 3 hours, and then hot rolled at 430°C with a 90% reduction, with 6 rolling passes. (4) The rolled sample is solutionized at 510°C for 1 hour. (5) The solutionized sample is pre-deformed by 5% cold stretching, and then aged at 165°C for 20 hours.
[0054] The aluminum-lithium alloy of this comparative example was subjected to a long-term heat exposure test, specifically: after the sample was heat exposed at 250° C. for 100 hours, a room temperature tensile property test was performed. The mechanical properties of the sample are shown in Table 1.
[0055] The microstructure of the aluminum-lithium alloy of this comparative example was characterized. The data of the grain size, grain boundary density after high temperature solution treatment and T1 phase size after heat exposure test are shown in Table 1.
[0056] The IPF diagram and grain boundary distribution diagram of the comparative aluminum-lithium alloy after thermal exposure test are shown in Figure 3 The TEM photo of the matrix precipitation phase of the aluminum-lithium alloy of this comparative example after the heat exposure test is shown in (b1, b2). Figure 5 (b) is shown. The fracture photo of the aluminum-lithium alloy of this comparative example after tensile testing is shown in Figure 6 (c) as shown.
[0057] Comparative Example 2 The material of this comparative example is Al-2.3Cu-0.9Li-0.4Mg-0.17Sc-0.12Zr, but conventional hot working and heat treatment processes are used. The preparation steps include: (1) Argon protection smelting, conventional metal mold casting to obtain an ingot. (2) The ingot is homogenized at 420°C for 15 hours, then homogenized at 460°C for 18 hours, and then the ingot is peeled to obtain a peeled ingot. (3) The peeled ingot is preheated at 460°C for 3 hours, and then hot rolled at 460°C with a 90% reduction, with 6 rolling passes. (4) The rolled sample is solutionized at 525°C for 1.5 hours. (5) The solutionized sample is pre-deformed by 4% cold stretching, and then aged at 160°C for 25 hours.
[0058] The aluminum-lithium alloy of this comparative example was subjected to a long-term heat exposure test, specifically: after the sample was heat exposed at 250° C. for 100 hours, a room temperature tensile property test was performed. The mechanical properties of the sample are shown in Table 1.
[0059] The microstructure of the aluminum-lithium alloy of this comparative example was characterized. The data of the grain size, grain boundary density after high temperature solution treatment and T1 phase size after heat exposure test are shown in Table 1.
[0060] The SEM photo of the aluminum-lithium alloy in this comparative example after solution treatment is as follows Figure 2 (c) As shown. The IPF diagram and grain boundary diagram of the aluminum-lithium alloy of this comparative example after high temperature solution treatment are shown in Figure 3 (c1, c2) As shown. The TEM photo of the precipitated phase of the aluminum-lithium alloy of this comparative example after the heat exposure test is as follows Figure 5 (c) As shown. The fracture photo of the aluminum-lithium alloy of this comparative example after tensile testing is shown Figure 6 (d) as shown.
[0061] Comparative Example 3 The material of this comparative example is Al-2.4Cu-1Li-0.4Mg-0.15Sc, without adding Zr element, and adopts the hot processing process of "preliminary hot rolling-medium temperature solid solution-aging treatment-medium temperature rolling" and the high temperature solid solution treatment process 10°C below the melting point, including the following preparation steps: (1) Argon protection smelting, conventional metal mold casting to obtain ingots. (2) The ingot is homogenized at 420°C for 15 hours, and then homogenized at 460°C for 18 hours, and then the ingot is peeled to obtain a peeled ingot. (3) The ingot is preheated at 460°C for 3 hours, and then hot rolled at 460°C with a 30% reduction, and the rolling passes are 3 times. After the hot rolling is completed, the hot-rolled billet is oil-quenched to room temperature within 15 seconds to complete the medium temperature solid solution. (4) The billet is placed in a 120°C aging furnace for 15 hours. (5) The aged slab was preheated at 250℃ for 2 hours, and then medium-temperature rolled at 250℃ with a reduction of 50%, and the number of rolling passes was 5. (6) The melting point of the alloy was calculated to be 575℃ using ThermoCalc software, and the rolled sample was solution treated at 565℃ for 1.5 hours. (7) The solution treated sample was cold stretched by 5%, and then aged at 155℃ for 25 hours.
[0062] The aluminum-lithium alloy of this comparative example was subjected to a long-term heat exposure test, specifically: after the sample was heat exposed at 250° C. for 100 hours, a room temperature tensile property test was performed. The mechanical properties of the sample are shown in Table 1.
[0063] The microstructure of the aluminum-lithium alloy of this comparative example was characterized. The data of the grain size, grain boundary density after high temperature solution treatment and T1 phase size after heat exposure test are shown in Table 1.
[0064] The IPF diagram and grain boundary diagram of the aluminum-lithium alloy in this comparative example after high temperature solution treatment are shown in Figure 3 (d1, d2) is shown. The fracture photo of the aluminum-lithium alloy of this comparative example after tensile testing is shown in Figure 6 (e) as shown.
[0065] Comparative Example 4 The material of this comparative example is Al-3.5Cu-1Li-0.3Mg-0.28Sc-0.21Zr, and the hot working process of "preliminary hot rolling-medium temperature solution-aging treatment-medium temperature rolling" and the high temperature solution treatment process below the melting point by 10°C are adopted, including the following preparation steps: (1) Argon protection smelting, conventional metal mold casting to obtain an ingot. (2) The ingot is homogenized at 420°C for 17 hours, and then homogenized at 460°C for 23 hours, and then the ingot is peeled to obtain a peeled ingot. (3) The peeled ingot is preheated at 460°C for 5 hours, and then hot rolled at 460°C with a reduction of 30%, with 3 rolling passes. After the last hot rolling pass is completed, the hot rolled billet is oil-quenched to room temperature within 15 seconds to complete the medium temperature solution. (4) The quenched rolled piece is placed in an aging furnace at 110°C for 15 hours. (5) The aged rolled piece was preheated at 250°C for 2 hours, and then medium-temperature rolled at 250°C with a reduction of 40%, with 4 passes. (6) The melting point of the alloy was calculated to be 550°C using ThermoCalc software, and the rolled sample was solution treated at 542°C for 1 hour. (7) The solution treated sample was cold stretched by 6%, and then aged at 165°C for 22 hours.
[0066] The aluminum-lithium alloy of this comparative example was subjected to a long-term heat exposure test, specifically: after the sample was heat exposed at 250° C. for 100 hours, a room temperature tensile property test was performed. The mechanical properties of the sample are shown in Table 1.
[0067] The microstructure of the aluminum-lithium alloy of this comparative example was characterized. The data of the grain size, grain boundary density after high temperature solution treatment and T1 phase size after heat exposure test are shown in Table 1.
[0068] The SEM photo of the aluminum-lithium alloy in this comparative example after high temperature treatment is as follows Figure 2 (d) As shown. The TEM photo of the matrix precipitation phase of the aluminum-lithium alloy of this comparative example after the heat exposure test is as follows Figure 5 (d) as shown.
[0069] Table 1
[0070] Combined with the measured data in Table 1, it can be seen that after a long-term heat exposure test at 250°C for 100 hours, Examples 1 and 2 have better strength, plasticity and strength-plasticity product than the alloys of Comparative Examples 1 to 4. This is because the T1 phase in the example alloys has better coarsening resistance, smaller grain size and higher grain boundary density. Figure 1 It can be seen that “preliminary hot rolling-medium temperature solution-aging treatment” can construct dense nano-sized T1 phase in the matrix with an average size of 18nm. Figure 2 (a, b) It can be seen that through reasonable design of Cu, Sc, and Zr components and high-temperature solution treatment process only 7~12℃ below the melting point, the brittle phase in the matrix can be basically dissolved. Figure 4 It can be seen that after thermal exposure, the grain boundary precipitated phase can be gathered at the subgrain boundary and precipitated. Because the grain boundary density of the embodiment is very high, the damage to the grain boundary caused by the grain boundary precipitated phase and Li element segregation can be diluted. Figure 6 (a, b) It can be seen that the fracture surface of the embodiment shows ductile fracture characteristics, and dense and fine dimples can be seen from the local enlarged image.
[0071] The comparison between Comparative Example 1 and Examples 1 and 2 highlights the benefits of the composition design and thermal processing and heat treatment processes of the examples on the heat resistance, heat resistance and strength-ductility product of the alloy. Figure 3 (b1, b2) shows that the larger grain size and lower grain boundary density lead to the low elongation of this comparative example. Figure 5 (b) It can be seen that the more serious coarsening of the T1 phase leads to a lower tensile strength in this comparative example. Figure 6 (c) It can be seen that the fracture of this comparative example shows standard brittle intergranular fracture characteristics. In general, the strength-ductility product of this comparative example is about 67.2% lower than that of Example 1.
[0072] The comparison between Comparative Example 2 and Examples 1 and 2 shows that the composition design of the examples needs to be combined with thermal processing and heat treatment processes to achieve better results. Figure 2 (c) It can be seen that when the high-temperature solution treatment temperature is not high enough, some brittle intermediate phases will remain in the matrix, which will damage the plasticity; combined with Figure 3 (c) It can be seen that when the hot working process of "initial hot rolling-medium temperature solution treatment-aging treatment-medium temperature hot rolling" is not used, the grain size after solution treatment will be significantly larger than that of the embodiment, and the grain boundary density will be lower than that of the embodiment, which will also lead to reduced plasticity. Figure 6 (d) It can be seen that the brittle fracture characteristics in the fracture of this comparative example are also quite obvious. Figure 2 (c) and Figure 5(c) It can be seen that the undissolved brittle phase will waste some Sc and Zr elements, and the effect of inhibiting the coarsening of the T1 phase will be weakened, which reduces the heat resistance of this comparative example. Overall, compared with Example 1, the strength-ductility product of this comparative example is about 39.2% lower.
[0073] The comparison between comparative example 3 and examples 1 and 2 shows that the combined addition of Sc and Zr elements can achieve better results. Figure 3 (d1, d2) shows that when only Sc element is added, the grain size of this comparative example is larger and the remaining subgrain boundaries are very few. This makes the grain boundary density of this comparative example reduced by 33.6% and the elongation reduced by about 24.7% compared with Example 1. Figure 6 (e) It can be seen that the fracture surface of this comparative example shows obvious brittle fracture characteristics.
[0074] The comparison between Comparative Example 4 and Examples 1 and 2 shows that the elements Cu, Sc and Zr need to be added according to the requirements of the examples to achieve better results. Figure 2 (d) It can be seen that the excessively high content of Cu, Sc, and Zr produces a large amount of brittle phases in the alloy matrix. Even after high-temperature solution treatment, these brittle phases cannot be dissolved, which seriously damages the plasticity of the alloy. Compared with Example 1, the elongation of this comparative example is reduced by about 49.4%.
[0075] It should be pointed out that for ordinary technicians in this technical field, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of this application should be included in the protection scope of this application.
Claims
1. A method for preparing a high-strength and high-plasticity heat-resistant aluminum-lithium alloy, characterized in that: The following steps are involved: Step 1: smelting the ingredients according to the alloy composition, casting and forming an ingot, wherein the ingot includes, by mass percentage, Cu 1.8-2.5%, Li 0.8-1.2%, Mg 0.1-0.5%, Sc 0.1-0.2%, Zr 0.05-0.15%, other impurity elements ≤0.1%, and the balance is Al, performing a two-stage homogenization treatment on the ingot, and then performing a peeling treatment on the ingot to obtain a peeled ingot; Step 2: preliminarily hot rolling the peeled ingot at 450-470° C., and after the hot rolling, oil-quenching the hot-rolled billet to room temperature within 15 seconds to complete medium-temperature solution treatment; Step 3, performing a first aging treatment on the rolled slab after the medium temperature solution treatment; Step 4, heating the rolled billet after the first aging treatment to 220-250° C. for insulation, and performing medium-temperature hot rolling at 220-250° C.; Step 5, performing high temperature solution treatment, wherein the temperature of the high temperature solution treatment is 7-12°C lower than the melting point of the aluminum-lithium alloy; Step six, performing 3-6% cold stretching pre-deformation, and then performing a second aging treatment to obtain the aluminum-lithium alloy.
2. The method for preparing a high-strength and high-ductility heat-resistant aluminum-lithium alloy according to claim 1, characterized in that: In the two-stage homogenization treatment, the temperature of the first stage homogenization treatment is 400~420℃, the insulation time is 12~24 hours, and the temperature of the second stage homogenization treatment is 450~500℃, the insulation time is 15~30 hours.
3. The method for preparing a high-strength-plasticity heat-resistant aluminum-lithium alloy according to claim 1, characterized in that: Before the initial hot rolling, the ingot is preheated at 450-470°C for 3-10 hours.
4. The method for preparing a high-strength and high-ductility heat-resistant aluminum-lithium alloy according to claim 1, characterized in that: The reduction of hot rolling is 20~40%, and the number of rolling passes is 2~4 times.
5. The method for preparing a high-strength-ductility-heat-resistant aluminum-lithium alloy according to claim 1, characterized in that: The temperature of the first aging treatment is 100~120℃, and the treatment time is 15~20 hours.
6. The method for preparing a high-strength-ductility-heat-resistant aluminum-lithium alloy according to claim 1, characterized in that: The insulation time of step 4 is 1 to 3 hours.
7. The method for preparing a high-strength-plasticity heat-resistant aluminum-lithium alloy according to claim 1, characterized in that: The reduction of medium temperature hot rolling is 40~60%, and the rolling passes are 4~7 times.
8. The method for preparing a high-strength-ductility-heat-resistant aluminum-lithium alloy according to claim 1, characterized in that: The time of high temperature solution treatment is 1 to 1.5 hours.
9. The method for preparing a high-strength-ductility-heat-resistant aluminum-lithium alloy according to claim 1, characterized in that: The temperature of the second aging treatment is 150~165℃, and the treatment time is 15~25 hours.
10. A high-strength, high-plasticity, heat-resistant aluminum-lithium alloy, characterized in that: It is the aluminum-lithium alloy obtained according to the preparation method of the high-strength-plasticity heat-resistant aluminum-lithium alloy according to any one of claims 1 to 9. After a long-term heat exposure test at 250°C for 100 hours, its tensile strength is not less than 346MPa, its elongation is not less than 15.6%, and its strength-plasticity product is not less than 5397.6MPa%.
Citation Information
Patent Citations
Thermal treatment process for improving comprehensive performance of aluminum-lithium alloy
CN106591632A
A scandium-containing cast aluminum-lithium alloy and a preparation method thereof
CN108570579A
Preparation process for improving comprehensive performance of aluminum-lithium alloy product
CN110423966A
Damage-resistant aluminum lithium alloy and preparation method and application thereof
CN115747590A
High-strength heat-resistant aluminum-lithium alloy and preparation method thereof
CN117107133A
Cited By
Heat-resistant Al-Cu-Mg-Mn aluminum alloy and preparation method and application thereof
CN122303702A